Cloud Based Real Time Anti Vehicle Theft By Using LP Recognition And OCR Recognition (International Journal of Engineering and Computer Science, 2017)
A real time Anti-Vehicle theft using LP Recognition in cloud is an image processing technique with cloud computing environment which uses license plate to identify the theft vehicle. The proposed system of this paper is on recognition of LP (License Plate) number and authentication of the license plate number to make human work easier. The main objective of the system is to improve efficient automatic theft vehicle identification system by using the vehicle LP number. It is widely used in various areas such as traffic signals, toll booths and surveillance. The algorithm consists of major parts: Extraction and Segmentation, Template Matching and Authentication, Vehicle identification, The LP characters are recognized and compare with cloud database environment. It helps police and military forces to locate whether license plate number is registered or not and shows owner name and address, place of registration. The system will be going to implemented and simulated in Mat lab, and its performance is testing on a real static and dynamic images.